Original paper Left atrial appendage occlusion using the PLAATO system in high-risk patients with atrial fibrillation – long-term follow-up - Kukuła, Krzysztof; Kłopotowski, Mariusz; Konka, Marek; Witkowski, Adam; Rużyłło, Witold (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2009)
Background: Vitamin K antagonists (VKA) remain the treatment of choice for stroke prevention in high-risk AF patients. However, there is a large proportion of patients who are not receiving VKA because of comorbidities or past adverse events. In such cases percutaneous left atrial appendage (LAA) occlusion has been proposed as an alternative to VKA. The concept was based on the fact that approximately 90% of all thrombi originate in the left atrial appendage. Aim: The aim of the study was to assess the long-term safety and efficacy of percutaneous LAA closure using the PLAATO device. Methods: Six high-risk AF patients, in whom an attempt was made to close the LAA using the PLAATO device, were included in the study. Follow-up data were obtained during patient visits and by telephone interview. The study was performed as part of the original European PLAATO Study. Results: Of the 6 patients in whom device implantation was attempted, percutaneous LAA occlusion was successful in 5 cases (83.3%). The procedure failed in one patient because of unusual LAA anatomy. There were no periprocedural complications. The average CHADS2 score of the five treated patients was 3.0 (range 2 to 5). Median follow-up was 54 months and ranged from 48 to 59 months. All patients discontinued VKA. No patients died. There were no cases of ischaemic stroke. There were no cases of intracranial or gastrointestinal bleeding. Conclusions: Percutaneous LAA closure with the PLAATO device is a feasible procedure and seems to prevent ischaemic stroke in high-risk AF patients. However, large, randomized studies are needed to prove its true benefit.